Regio- and stereoselective access to highly substituted vinylphosphine oxides via metal-free electrophilic phosphonoiodination of alkynes - Bingbing Dong; Fengqian Zhao; Wen-Xin Lv; Ying-Guo Liu; Donghui Wei; Junliang Wu; Yonggui Robin Chi (Nature Communications, 2024)
Abstract In general, the P-centered ring-opening of quaternary phosphirenium salts (QPrS) predominantly leads to hydrophosphorylated products, while the C-centered ring-opening is primarily confined to intramolecular nucleophilic reactions, resulting in the formation of phosphorus-containing cyclization products instead of difunctionalized products generated through intermolecular nucleophilic processes. Here, through the promotion of ring-opening of three-member rings by iodine anions and the quenching of electronegative carbon atoms by iodine cations, we successfully synthesize β-functionalized vinylphosphine oxides by the P-addition of QPrS intermediates generated in situ. Multiple β-iodo-substituted vinylphosphine oxides can be obtained with exceptional regio- and stereo-selectivity by reacting secondary phosphine oxides with unactivated alkynes. In addition, a variety of β-functionalized vinylphosphine oxides converted from C-I bonds, especially the rapid construction of benzo[b]phospholes oxides, demonstrates the significance of this strategy.